2017
DOI: 10.14196/mjiri.31.54
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Joel-Cohen-based technique and the transverse Pfannenstiel for caesarean section for safety and effectiveness: A systematic review and meta-analysis

Abstract: Background: Caesarean section (C-section) is the most common surgery among women worldwide, and the global rate of this surgical procedure has been continuously rising. Hence, it is significantly crucial to develop and apply highly effective and safe caesarean section techniques. In this review study, we aimed at assessing the safety and effectiveness of the Joel-Cohen-based technique and comparing the results with the transverse Pfannenstiel incision for C-section. Methods: In this study, various reliable da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Previous meta-analyses have grouped all Joel-Cohen based methods (Joel-Cohen method, MLM, and MMLM) within one cohort, therefore limiting conclusions with the inability to separate the methods. 45,46 The findings of this meta-analysis provide evidence to demonstrate favorability of the MLM and MMLM techniques over PKM.…”
Section: Main Findingsmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous meta-analyses have grouped all Joel-Cohen based methods (Joel-Cohen method, MLM, and MMLM) within one cohort, therefore limiting conclusions with the inability to separate the methods. 45,46 The findings of this meta-analysis provide evidence to demonstrate favorability of the MLM and MMLM techniques over PKM.…”
Section: Main Findingsmentioning
confidence: 72%
“…This meta‐analysis is the first to separate MLM and MMLM in their comparison to PKM, with findings of MLM and MMLM to be favourable over PKM in operative time, blood loss, and length of hospital stay. Previous meta‐analyses have grouped all Joel‐Cohen based methods (Joel‐Cohen method, MLM, and MMLM) within one cohort, therefore limiting conclusions with the inability to separate the methods 45,46 . The findings of this meta‐analysis provide evidence to demonstrate favorability of the MLM and MMLM techniques over PKM.…”
Section: Discussionmentioning
confidence: 84%
“…Caesarean section is the most common surgery among women worldwide, with the global rate rising. 34 In a recent meta-analysis, Sobhy et al 35 reported the risk of maternal death after caesarean section at 7.6 per 1000 procedures (95% CI 6.6-8.6) with the highest burden in sub-Saharan Africa. In LMICs, one in every 100 women dies after caesarean section whereas in high-income countries, there are eight maternal deaths per 100,000 caesarean sections.…”
Section: Caesarean-section Birthmentioning
confidence: 99%